2010
DOI: 10.3899/jrheum.090652
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease Associated with Anti-PM/Scl or Anti-Aminoacyl-tRNA Synthetase Autoantibodies: A Similar Condition?

Abstract: Anti-PM/Scl and anti-ARS antibodies are associated with similar clinical manifestations, with the exception only of more overt myositis in the latter, therefore challenging the clinical specificity of the antisynthetase syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 44 publications
5
49
1
5
Order By: Relevance
“…Raynaud's phenomenon, palmar telangiectasia, distal digital tip ulceration and digital oedema are specific physical findings that are often seen in systemic sclerosis [23,24] but rarely seen in IIP. Similarly, the features of digital fissuring ("mechanic hands") ( figure 1) and a fixed rash on the digital extensor surfaces (Gottron's sign) (figure 2) are hallmarks of the anti-synthetase syndrome or systemic sclerosis-myositis overlap associated with PM-Scl antibody positivity [16,[25][26][27][28][29][30][31][32]. The use of nailfold microscopy in the evaluation of individuals with Raynaud's phenomenon is encouraged as capillary loop abnormalities can be predictive of developing a CTD such as systemic sclerosis or dermatomyositis [33][34][35][36].…”
Section: Clinical Domainmentioning
confidence: 99%
“…Raynaud's phenomenon, palmar telangiectasia, distal digital tip ulceration and digital oedema are specific physical findings that are often seen in systemic sclerosis [23,24] but rarely seen in IIP. Similarly, the features of digital fissuring ("mechanic hands") ( figure 1) and a fixed rash on the digital extensor surfaces (Gottron's sign) (figure 2) are hallmarks of the anti-synthetase syndrome or systemic sclerosis-myositis overlap associated with PM-Scl antibody positivity [16,[25][26][27][28][29][30][31][32]. The use of nailfold microscopy in the evaluation of individuals with Raynaud's phenomenon is encouraged as capillary loop abnormalities can be predictive of developing a CTD such as systemic sclerosis or dermatomyositis [33][34][35][36].…”
Section: Clinical Domainmentioning
confidence: 99%
“…A number of studies investigating several systemic autoimmune diseases or overlap syndromes have shown that the presence of the anti-PM/Scl autoantibody is associated with pulmonary conditions, 11,15,[17][18][19]25,[28][29][30] joint conditions, 5,11,15,18,30 Raynaud's phenomenon, 11,15,18,30,31 "mechanic hands" 17,18,25,[28][29][30] and/or plantar hyperkeratosis. 5,7,11,13,[17][18][19] In this respect, the phenotypic manifestation of this autoantibody resembles that of antisynthetase syndrome.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Кроме того, в сыворотке больных, страдающих ревматиче-скими заболеваниями, сопровождающимися мышечным повреждением, определяются и миозит-ассоциированные антитела [12][13][14][15][16].…”
Section: классификацияunclassified